To solve the equation
\[ \frac{3}{2}(4 - 8x) + 5x = 1 - 7x, \]
we will follow step-by-step justification using the properties of equality and simplify the equation.
-
Distribute \(\frac{3}{2}\) on the left side:
\[ \frac{3}{2} \cdot 4 - \frac{3}{2} \cdot 8x + 5x = 1 - 7x \]
Simplifying gives:
\[ 6 - 12x + 5x = 1 - 7x \]
-
Combine like terms on the left side:
\[ 6 - 7x = 1 - 7x \]
-
Add \(7x\) to both sides to isolate the constant:
\[ 6 = 1 \]
-
Subtract 1 from both sides:
\[ 6 - 1 = 0 \quad \Rightarrow \quad 5 = 0 \]
Since \(5 = 0\) is a contradiction (this statement is false), it indicates that there are no values of \(x\) that can satisfy the original equation.
Thus, the number of solutions to the equation is:
\[ \boxed{0} \]